2018
DOI: 10.5194/acp-2018-745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphology, Chemical Composition and Mixing State of Atmospheric Aerosols from Two Contrasting Environments in Southern India

Abstract: Abstract. The state of mixing of aerosols significantly influence their transformation, deposition, radiative forcing and health effects. We report the realistic (as in the atmosphere) state of mixing and morphology of aerosols at two nearby but contrasting environments; the urban region Bengaluru and a remote region Challakere. Ambient aerosols are collected on filter substrates using a High-Volume Sampler and analysed using Scanning Electron Microscope 15 (SEM) equipped with Energy Dispersive X-Ray spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In a stricter sense, the diurnal variation in emissions of BC as well as the adjustment factor would vary from station to station depending upon the nature of sources and mesoscale meteorology running over the synoptic scale (Govardhan et al, 2016). Thus, the modified emissions may not necessarily improve the model's performance 5 homogeneously throughout the study domain. This is especially clear from disagreements that still persists between model (DIEM+AF configuration) and the observations at a few stations ( fig.2d Chennai May, fig.2i.…”
Section: Effects Of Modified Emissions On Nsbc: Model Vs Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a stricter sense, the diurnal variation in emissions of BC as well as the adjustment factor would vary from station to station depending upon the nature of sources and mesoscale meteorology running over the synoptic scale (Govardhan et al, 2016). Thus, the modified emissions may not necessarily improve the model's performance 5 homogeneously throughout the study domain. This is especially clear from disagreements that still persists between model (DIEM+AF configuration) and the observations at a few stations ( fig.2d Chennai May, fig.2i.…”
Section: Effects Of Modified Emissions On Nsbc: Model Vs Observationsmentioning
confidence: 99%
“…Another important parameter is the assumptions about state of mixing of aerosol in general and BC in particular which significantly governs the resulting optical and radiative effects 15 of aerosol (Jacobson, 2001;Chandra et al, 2004;Peng et al, 2016). In these regards, the realistic state of mixing of aerosol over the Indian region (as revealed by a recent study (Hariram et al, 2018) could be examined and prescribed in the models to reveal its role in unrealistic simulations of AOD. This study has also revealed an important information about response of NSBC mass concentration to the changes in emissions.…”
Section: Effects Of Modified Bc Emissions On the Simulated Aodmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that the largest volume fraction (34.216 %) of particles captured is in the outer layer. Moreover, it is also estimated that about 65 % of the volume fraction of particles is found in the top two layers of the filter (Beatriz et al 2016). Additionally, it is reported that, the inner layers are found to trap only the fine particles of mean particle diameter 0.533 µm.…”
mentioning
confidence: 99%
“…We, on the other hand, are interested to study the morphology and state of mixing of dust-BC composite aerosol system (dust particles with BC depositions), which mainly falls under coarse mode aerosols. A recent study (Beatriz et al 2016) has reported that quartz fiber filters efficiently collect particles of different size ranges in the top layer ranging from diameter of 0.199 µm to 10.272 µm. It is also reported that the largest volume fraction (34.216 %) of particles captured is in the outer layer.…”
mentioning
confidence: 99%